Singularities of Analytic Spaces - Tognoli, A. (C.I.M.E. Summer Schools, 2011)
Lazzeri: Analytic singularities.- V. Poenaru: Lectures of the singularities of C? mappings.- A. Tognoli: About the set of non coherence of a real analytic variety. Pathology and imbedding problems for real analytic spaces.